THE FUTURE OF PALLIATIVE CARE: USING A NOVEL APPROACH TO PREPARE THE WORKFORCE. Issue 1 (1st March 2015) - Roberts, A; Gambles, M; Hellaby, M
Abstract : Introduction: The delivery of world class palliative care dying requires the workforce to have substantial technical knowledge, clinical skill & excellent communication skills. Aim(s) and method(s): To develop, pilot and evaluate an MDT simulation course focused on care in the last days of life. The bespoke course consisted of e-learning & a study day focusing on 4 scenarios simulating the last days of life in a hospital setting. It was piloted on 2 occasions. Evaluation included pre & post course questionnaires & thematic analysis of post course focus group interviews. Results: Twelve participants completed the training and 11 participated in focus groups immediately following the training. Participants were overwhelmingly positive about the course, valuing the realism, small group size, & MDT nature of the training. Feedback and the opportunity for reflection including video recording were also highly valued. Participants were fairly knowledgeable & held generally positive perceptions of caring for dying patients prior to the training. The greatest shift pre to post training was the reduction of participants' level of perceived helplessness when caring for dying patients. Confidence in all three domains (Communication, Management of the Patient, MDT Working) was relatively high (around 60%) pre-training, particularly for MDT working. It rose immediately post training (T2) in all domains but especially with regard to communication with the family & the provision of and referral for spiritual care. Conclusions: The sample was small but the course was universally valued by participants. Findings have been used to refine the course and evaluation of further courses is planned.